2021
DOI: 10.2215/cjn.03940321
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polypharmacy with Kidney Disease Progression in Adults with CKD

Abstract: Background and objectivePolypharmacy is common in patients with CKD and reportedly associated with adverse outcomes. However, its effect on kidney outcomes among patients with CKD has not been adequately elucidated. Hence, this investigation was aimed at exploring the association between polypharmacy and kidney failure requiring KRT.Design, setting, participants, and measurementsWe retrospectively examined 1117 participants (median age, 66 years; 56% male; median eGFR, 48 ml/min per 1.73 m2) enrolled in the Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 41 publications
(45 reference statements)
3
20
0
1
Order By: Relevance
“…Our results showed that elderly people with excessive polypharmacy (more than ten medications) are six times more likely to have renal impairment compared to elderly with less than ve medications. This is consistent with the literature, which shows that polypharmacy exposure is signi cantly associated with an increased risk of kidney dysfunction (7,28,29). Knowing that pharmacokinetic changes happen with aging, where renal elimination decreases, increases the risk of pharmaceutical ingredient and metabolite accumulation, which in this case increases the risk of renal impairment (9).…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that elderly people with excessive polypharmacy (more than ten medications) are six times more likely to have renal impairment compared to elderly with less than ve medications. This is consistent with the literature, which shows that polypharmacy exposure is signi cantly associated with an increased risk of kidney dysfunction (7,28,29). Knowing that pharmacokinetic changes happen with aging, where renal elimination decreases, increases the risk of pharmaceutical ingredient and metabolite accumulation, which in this case increases the risk of renal impairment (9).…”
Section: Discussionsupporting
confidence: 86%
“…In CKD, this adaptive response is lost, and a decrease in transporter expression is observed [33], possibly caused by aberrant gut-to-kidney signaling through increased blood concentrations of uremic toxins [34]. This assumption is further supported by recent observations in which protein-bound uremic toxins may compete with co-administered drugs commonly used in CKD management, which potentially compromise the residual tubular function [25,35,36]. The progressive loss of tubular function and accompanied increase in retention of uremic toxins fuel systemic metabolic disorders and comorbidities associated with the pathophysiology of CKD.…”
Section: Remote Sensing and Signaling: Linking The Kidney To The Gutmentioning
confidence: 88%
“…A previous cohort comprised of U.S. adults aged ≥45 years with a 5-year follow-up showed that only major polypharmacy (≥ 8 medications) was associated with increased mortality (HR = 1.24 [1.06, 1.45]), but not for minor polypharmacy (6-7 medications) (HR = 1.15 [0.98, 1.36]) in those with CKD, and there was no evidence that this association was modified by CKD status (22). Another Japanese cohort consisting of 1,117 participants reported that both polypharmacy (5-9 medications) and hyperpolypharmacy (≥10 medications) were associated with kidney failure (HR = 2.28 [1.00, 5.21] and HR = 2.83 [1.21, 6.66], respectively), but only hyperpolypharmacy was related to all-cause mortality (HR = 2.80 [1.41-5.54]) (21). However, our sensitivity analysis suggested even minor polypharmacy significantly increased mortality in the elderly CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, evidence on polypharmacy and health outcomes in older adults with CKD is scarce. Several cohort studies indicated polypharmacy was associated with an increased risk of kidney failure, fragility fracture, CVD events, and all-cause mortality in patients with CKD (20)(21)(22), even regardless of CKD status (20,22,23).…”
Section: Introductionmentioning
confidence: 99%